Affective characteristics for 21st century learning environments: do they matter? - Wong, Su Luan (Kassel University Press, 2020)
Twenty-first century learners are media-centric and heavily reliant on technology. Internet-accessible resources are always at the students’ finger-tips and they learn through such resources anywhere, anytime. Unfortunately, formal education in most part of Asia remains largely examination focused given the immense pressure to obtain paper qualifications. Our challenge today is how do we make students learn on their own volition? How do we then sustain learning when the education system is still very much examination-centric? Success in learning is not always dependent on the ways students are taught in the classroom or the tools they use to learn but can be very much affected by the learners’ affective characteristics. This paper highlights two selected affective characteristics — attitudes and interest, as previous and current literature continue to suggest their positive impact on student behavior including learning.